Analysis of Single-Use Hemodialysis Tariff Determination Based on INA-CBG: A Case Study at Siaga Medika Banyumas General Hospital - Nur Fitri Margaretna; Arlette Suzy Puspa Pertiwi; Oke Andikarya (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing prevalence of Chronic Kidney Disease (CKD) has led to a rising demand for hemodialysis services, most of which are financed by the Indonesian National Health Insurance (BPJS Kesehatan) through the INA-CBG tariff system. However, the discrepancy between INA-CBG tariffs and the actual service costs—particularly due to the use of single-use dialyzers—poses financial challenges for private hospitals. This study aims to analyze the operational costs, tariff differences, and financial feasibility of single-use hemodialysis services at Siaga Medika Banyumas General Hospital. A qualitative descriptive-exploratory approach was employed through in-depth interviews, observations, and document analysis involving five key informants. The results indicate that the largest cost component comes from medical consumables, especially dialyzers. A comparison revealed that the actual service cost was IDR 660,138, which is lower than the INA-CBG tariff of IDR 875,000 and the hospital’s own tariff of IDR 1,877,536. The cost recovery rate (CRR) analysis yielded 132.54% for BPJS patients and 284.4% for general (non-BPJS) patients, indicating profitability. The hospital’s strategies include logistics efficiency, adjustments in non-BPJS tariffs, and resource optimization. The study concludes that the single-use hemodialysis service at Siaga Medika Banyumas General Hospital is financially viable, although it requires strict cost management and more accurate tariff policy support to ensure service sustainability.